How can three dimensional computing inform the industrial design process / Shahriman Zainal Abidin - Zainal Abidin, Shahriman (UiTM Kedah, 2003)
The new millennium era has made the computer an indispensable tool for everyone from every walk of life. In Industrial Design specifically, 3D Computing / Three Dimensional Computing or better known as CAD/CAM (Computer Aided Design and Manufacturing) is still considered an infant but the demand for it has been increasingly encouraging. It has become reliant on computer technologies and is responding to every change and need of customers.